Influence of oxygen levels on chondrogenesis of porcine mesenchymal stem cells cultured in polycaprolactone scaffolds. Issue 6 (27th March 2017) - Rodenas‐Rochina, Joaquin; Kelly, Daniel J.; Gómez Ribelles, Jose Luis; Lebourg, Myriam
Abstract: Chondrogenesis of mesenchymal stem cells (MSCs) is known to be regulated by a number of environmental factors, including local oxygen levels. The hypothesis of this study is that the response of MSCs to hypoxia is dependent on the physical and chemical characteristics of the substrate used. The objective of this study was to explore how different modifications to polycaprolactone (PCL) scaffolds influenced the response of MSCs to hypoxia. PCL, PCL‐hyaluronic acid (HA), and PCL‐Bioglass ® (BG) scaffolds were seeded with MSCs derived from bone marrow and cultured for 35 days under normoxic or low oxygen conditions, and the resulting biochemical properties of the MSC laden construct were assessed. Low oxygen tension has a positive effect over cell proliferation and macromolecules biosynthesis. Furthermore, hypoxia enhanced the distribution of collagen and glycosaminoglycans (GAGs) deposition through the scaffold. On the other hand, MSCs displayed certain material dependent responses to hypoxia. Low oxygen tension had a positive effect on cell proliferation in BG and HA scaffolds, but only a positive effect on GAGs synthesis in PCL and HA scaffolds. In conclusion, hypoxia increased cell viability and expression of chondrogenic markers but the cell response was modulated by the type of scaffold used. © 2017 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 105A: 1684–1691, 2017.